Turning yams into couscous - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Yams have a high water content and therefore do not keep well. This poor keeping quality is thought to be the principal constraint to the crop's development. But from Burkina Faso comes an idea to overcome this problem - processing yams into...